Development of a software module for automating the process of calculating water consumption and water disposal using the DYNAMO STUDIO development environment - T. A. Yurosheva; A. V. Kalinichenko (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to create a script for automating the processes of calculating water consumption and water disposal using the DYNAMO STUDIO development environment.Method. Solving modern problems in the field of automated construction design involves the consistent implementation of two types of processes: algorithmization and visualization.Result. The methods of operation of Dynamo scenarios are presented and described, which significantly speed up the calculation of water supply and sanitation, as well as the process of preparing project documentation. The principles of information modeling allow to increase the speed of design work and avoid a wide range of errors during design, which will not lead to corresponding problems at the stage of construction of the facility. The results of the application of the developed algorithms for automating the calculation of water consumption and sanitation are presented.Conclusion. Using the Dynamo Studio development environment allows you to create effective software modules for automating calculations of water consumption and sanitation. This will improve the quality of design and reduce the time required to complete routine tasks.